Pendampingan Mahasiswa dalam Meningkatkan Keterampilan Berbicara Bahasa Arab melalui Program Outing Class - Rosikh, Fahrur; Hermansyah, Yudisthira Ade; Rahmi, Aulia; Arisnaini, Arisnaini (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
Arabic speaking skills (maharah kalam) is an important aspect in Arabic learning, especially for students in college. However, there are still many students who have difficulty in speaking Arabic actively. This community service activity aims to describe the lecturer's assistance in improving students' speaking skills through the outing class program. This community service activity uses the participatory action research method. The results of the study showed that outing classes accompanied by lecturers intensively were able to increase students' courage in speaking, enrich vocabulary, and train speaking skills effectively. Students showed high enthusiasm for this method because the learning atmosphere became more enjoyable and contextual. In conclusion, assistance in the outing class program is an effective strategy in improving students' Arabic speaking skills and can be implemented sustainably as an alternative learning method.